The Effect of Green Innovation on Corporate Financial Performance: A Literature Review - Jia, Guo; Kassim, Aza Azlina Md (Journal of Theory and Practice of Management Science, 2024)
Heightening environmental challenges, increasing environmental awareness, and continuous refinement of environmental regulations have prompted corporations to increasingly focus on the development of green innovation in recent years. However, previous research has not reached a conclusive understanding of how green innovation affects corporate financial performance. In this case, this study seeks to categorize and summarize research conducted over the past five years on the relationship between green innovation and corporate financial performance, aiming to illustrate the reasons behind varied research conclusions.